2019
DOI: 10.1177/0258042x19890246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Company Characteristics on Human Resource Disclosure Index: Empirical Evidences from Indian Corporates

Abstract: Purpose: The purpose of the present research article is to know the extent of Human Resource (HR) disclosure practices and effects of various independent variables on HR disclosure practices in selected Indian listed companies. Design/methodology/approach: Initially, Human Resource Disclosure Index (HRDI) of 91 items is constructed for 63 companies listed on the NSE-100 index. After that, the effect of various independent variables is analyzed on HRDI. Finally, independent variables are regressed with HRDI to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 59 publications
6
25
0
Order By: Relevance
“…This implies that banks" profitability enhances the disclosure of human resource accounting ISSN 2162-3058 2020 information to various stakeholders. This result is consistent with the studies by Micah et al (2012), Akintoye (2012), Enofe et al (2013) and Aggarwal and Verma (2020) that showed a significant relationship between profitability and human resource accounting disclosure. Nevertheless, the results of the studies by Athanasios et al, (2013), Ullah and Karim (2015) and Sarkar et al, (2016) revealed no relationship.…”
Section: Discussion Of Findingssupporting
confidence: 93%
See 2 more Smart Citations
“…This implies that banks" profitability enhances the disclosure of human resource accounting ISSN 2162-3058 2020 information to various stakeholders. This result is consistent with the studies by Micah et al (2012), Akintoye (2012), Enofe et al (2013) and Aggarwal and Verma (2020) that showed a significant relationship between profitability and human resource accounting disclosure. Nevertheless, the results of the studies by Athanasios et al, (2013), Ullah and Karim (2015) and Sarkar et al, (2016) revealed no relationship.…”
Section: Discussion Of Findingssupporting
confidence: 93%
“…Currently, no verifiable evidence exists on the relationship between profitability and human resource accounting disclosure in Nigeria. Though, a significant positive relationship between profitability and human resource accounting disclosure has been consistently found by prior studies such as Syed (2009), Ahangar (2011), Rehman, Rehuman and Zaliad (2011), Micah et al, (2012), Akintoye (2012), Enofe et al, (2013) and Aggarwal and Verma (2020). However, Athanasios et al, (2013), Ullah and Karim (2015) and Sarkar et al, (2016) found an insignificant association between profitability and human resource accounting disclosure using regression analysis.…”
Section: Profitability and Human Resource Accounting Disclosuresupporting
confidence: 52%
See 1 more Smart Citation
“…The more disclosed information about the elements of companies' value creation the more investment tends to firms. And so, the companies are able to receive lower-priced funds [30,61,68] and trustworthy disclosure enhance value since it supports investor decision making [69]. In addition, that the larger companies are in the spotlight of the government agencies and society.…”
Section: Sizementioning
confidence: 99%
“…For that reason, better disclosure practices could be a way for companies to diminish the pressure [28]. There are number of empirical researches that examine the effect of size on human resources disclosure [3,28,30,63,65,68]. Hence the fourth hypothesis is proposed as: Hypothesis 4 (H4).…”
Section: Sizementioning
confidence: 99%